Pedagogies of Negation: Notes on the Politics of Refusal - Velasquez-Potts, Michelle C. (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2023)
This essay discusses a course I taught in 2021 at the University of Texas at Austin. The course, titled “The Politics of Refusal,” was prompted by my interest in exploring how pain, debility, and suffering, usually understood as limited and passive experiences, might also be generative and disruptive. The essay reflects on the trajectory of the class as the semester progressed. In particular, I pay attention to the dynamics of discussion as they relate to students’ relationship to theory and to disability and care. I consider what worked, what needed rethinking, and what possibilities were opened up for imagining new and creative ways to approach teaching theory during the COVID-19 pandemic.